2011
DOI: 10.1165/rcmb.2010-0089oc
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants Prevent the RhoA Inhibition Evoked by Crocidolite Asbestos in Human Mesothelial and Mesothelioma Cells

Abstract: Asbestos is a naturally occurring fibrous silicate, whose inhalation is highly related to the risk of developing malignant mesothelioma (MM), and crocidolite is one of its most oncogenic types. The mechanism by which asbestos may cause MM is unclear. We have previously observed that crocidolite in human MM (HMM) cells induces NF-kB activation and stimulates the synthesis of nitric oxide by inhibiting the RhoA signaling pathway. In primary human mesothelial cells (HMCs) and HMM cells exposed to crocidolite asbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Asbestos, which is the major environmental cause of malignant pleural mesothelioma, was shown to be involved in increased ROS levels within the pleura. It was subsequently suggested that asbestos-induced increased ROS levels was a major cause of the tumorigenesis of mesothelioma [ 35 ], and in vitro anti-oxidant treatment decreased invasive capacities of mesothelioma tumors [ 36 ]. Together with our results, these data suggest an interaction between BAP1 expression, ROS sensitivity and asbestos exposure [ 26 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Asbestos, which is the major environmental cause of malignant pleural mesothelioma, was shown to be involved in increased ROS levels within the pleura. It was subsequently suggested that asbestos-induced increased ROS levels was a major cause of the tumorigenesis of mesothelioma [ 35 ], and in vitro anti-oxidant treatment decreased invasive capacities of mesothelioma tumors [ 36 ]. Together with our results, these data suggest an interaction between BAP1 expression, ROS sensitivity and asbestos exposure [ 26 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…All the compounds under investigation were tested on three primary MPM cancer cell lines, derived from the pleural effusion of previously untreated patients suffering from MPM, namely BR95 (epithelioid), MM98 (sarcomatoid) [34,35] and MG06 (mixed with epithelioid predominance), and on a cisplatin-resistant cell line called MM98R derived from wild type MM98 by exposure to sub-lethal concentrations of cisplatin for several months [36]. Human mesothelial cells (HMC) were established by gently scraping the peritoneum of the inner wall of uncomplicated congenital hernia sacs surgically excised from premature babies (Pediatric Surgery Unit).…”
Section: Cell Culture and Growth Inhibition (Ic 50 )mentioning
confidence: 99%
“…RhoA regulates non-small lung cancer cell migration, but RhoA-related signal cascades in mesothelioma cells are inhibited by crocidolite, a type of asbestos 23 . Crocidolite activates NF-κB and promotes the nitric oxide synthesis by inhibiting the RhoA signalling pathway 24 . Furthermore, RhoA signalling inhibits the migration of breast cancer cells by decreasing stress fibres 25 .…”
Section: Discussionmentioning
confidence: 99%